Private sector antimalarial sales a decade after “test and treat”: A cross-sectional study of drug shop clients in rural Uganda - Shelus, Victoria; Mumbere, Nobert; Mulogo, Edgar M.; Barrington, Clare; Baguma, Emmanuel; Muhindo, Rabbison; Herrington, James E.; Emch, Michael; Maman, Suzanne; Boyce, Ross M. (Frontiers in Public Health, 2023)
Background: The World Health Organization has promoted “test and treat” guidelines for malaria since 2010, recommending all suspected malaria cases be confirmed with a parasitological test, typically a rapid diagnostic test (RDT), prior to treatment with antimalarial medications. However, many fevers at private drug shops in Uganda continue to be treated presumptively as malaria without diagnostic testing. Methods: The purpose of this study was to document private sector malaria case management in rural Uganda through a cross-sectional survey of drug shop clients in Bugoye sub-county. Drug shop vendors (n=46) recorded information about sales interactions with clients reporting fever or requesting antimalarials and collected capillary blood samples from clients who purchased medications without an RDT. We estimated the proportion of clients who purchased an RDT, adhered to the RDT result, and received antimalarials without having laboratory-confirmed malaria. Results: Most drug shops were unlicensed (96%) and sold RDTs (98%). Of 934 clients with suspected malaria who visited study drug shops during the data collection period, only 25% bought an RDT. Since some clients reported previous RDTs from the public sector, 40% of clients were aware of their malaria status at the drug shop. Among those with negative tests, 36% still purchased antimalarials. Sixty-five percent of clients who purchased an antimalarial without an RDT subsequently tested negative. Conclusions: Despite national guidelines, drug shop clients who purchase antimalarials from drug shops in Bugoye are often not tested to confirm a malaria diagnosis prior to treatment. Most clients treated presumptively with antimalarials did not have malaria. Interventions are needed to improve malaria case management and rational drug use in the private sector.